2019
DOI: 10.9734/ajacr/2019/v4i230110
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Physico-chemical Properties in Soil Samples of Prayagraj (Allahabad) District, Uttar Pradesh, India

Abstract: Physico-chemical properties of soils from different land use systems viz. agriculture, olericulture, horticulture etc in Prayagraj (Allahabad) Uttar Pradesh were analyzed in 2018-19. Samples were collected from 4 different sites of Allahabad district viz., ECC gaughat, Jhunsi, Karchhana & Subedarganj having distance between them of at least 4 kms. Some soils samples had higher water holding capacity & value of organic carbon. They have average value of pH and EC as compared to the cultivated soils. Pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Surface soils are having high amount of macro and micro pores compared to sub surface soils due to presence of high organic matter. Similar finding were reported by Verma et al, (2019) (26) . As presented in table 3 (18) .As depicted in table 3 and fig.…”
Section: Resultssupporting
confidence: 92%
“…Surface soils are having high amount of macro and micro pores compared to sub surface soils due to presence of high organic matter. Similar finding were reported by Verma et al, (2019) (26) . As presented in table 3 (18) .As depicted in table 3 and fig.…”
Section: Resultssupporting
confidence: 92%
“…The experimental results of the present investigation entitled "Assessment of Physico-Chemical properties of soil from different blocks of prakasam district Andhra Pradesh, India." The colour (Dry method) of soil samples is shown Brown, Dark brown, Yellowish red, red, yellowish brown, reddish brown, Light olive brown, Dark reddish brown, Dark red and in (Wet method) colour of soil samples was shown Dark brown, very dark, yellowish brown, Brown, very dark greyish brown, Yellowish red, Red, Dark yellowish-brown, reddish-brown these results are similar to Chahat Verma et al, [1]. The Soil Texture was sandy clay loam, sand content varied from 46-84%, silt 10-24% and clay 22.6-31% as reported by Das et al, [17].…”
Section: Soil Physical Propertiessupporting
confidence: 85%
“…Soil is a dynamic, 3-dimensional natural body of the landscape developed from the weathering of rocks through various pedogenic processes, composed of mineral and organic materials, processing a defined set of physical, chemical, and biological qualities, having a variable depth covering the earth's surface, and providing a medium for terrestrial plant growth [1]. Soil is a dynamic natural body formed by pedogenic processes such as rock weathering, and it is made up of mineral and organic ingredients with specific chemical, physical, and biological properties [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with agricultural sites, recreational sites characterized by a relatively higher human pressure had significantly ( p = 0.002) lower pH. Lower pH value could lead to dissolution of various contaminants, such as salts and metals, and cause detrimental effects on aquatic biota (Verma et al, 2012). The present study indicated that macroinvertebrate metrics which showed positive correlation with pH, such as TR, %EPT, BMWP score and H′, were significantly ( p < 0.05) lower in sampling sites with reduced pH value and higher disturbances (i.e.…”
Section: Discussionmentioning
confidence: 99%